2019
DOI: 10.3390/ijms20194914
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Hormones (FSH, LH, PRL, and GH) Differentially Regulate AQP5 Expression in Porcine Ovarian Follicular Cells

Abstract: This study aimed to examine the effect of follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), and growth hormone (GH) on Aquaporin 5 (AQP5) expression in granulosa (Gc) and theca cells (Tc) from medium (MF) and large (LF) ovarian follicles of pigs. The results showed that GH significantly decreased the expression of AQP5 in Gc from MF in relation to the control. In the Gc of large follicles, PRL stimulated the expression of AQP5. However, the increased expression of AQP5 in the Tc of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The present study aims to investigate the causes of the decreased oocyte competence during the NBS in buffalo. Many biological processes are required for developmental competence, with the exchange of information between oocyte and follicular environment promoting oocyte maturation 26 . Therefore, the focus of this study was to evaluate differences in the miRNA and transcriptomic profiles of OOs and corresponding FCs from buffalo ovaries collected in the BS and NBS.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aims to investigate the causes of the decreased oocyte competence during the NBS in buffalo. Many biological processes are required for developmental competence, with the exchange of information between oocyte and follicular environment promoting oocyte maturation 26 . Therefore, the focus of this study was to evaluate differences in the miRNA and transcriptomic profiles of OOs and corresponding FCs from buffalo ovaries collected in the BS and NBS.…”
Section: Discussionmentioning
confidence: 99%
“…Beside E2 and P4, prolactin (PRL) plays a major role in fluid production in the oviduct [22]. We recently found that PRL increased AQP5 mRNA and protein expression in the granulosa (GC) and theca cells (TC) obtained from medium (MF) and large follicles (LF) and in cocultures of these cells [23]. Prolactin had a stimulatory effect on AQP1 protein expression in the coculture of the abovementioned cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that PRL increased AQP5 mRNA and protein expression in the granulosa (GC) and theca cells (TC) obtained from medium (MF) and large follicles (LF) and in cocultures of these cells [23]. Prolactin had a stimulatory effect on AQP1 protein expression in the coculture of the abovementioned cells [23]. Moreover, we indicated the functional AQPs expression in these cells using swelling assay with an AQPs blocker, because a significant increase in the cell volume in hypotonic conditions treated with PRL was demonstrated when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of mammalian follicles is a key process in the ovary, and the proliferation and growth of GCs directly promotes follicular development [18]. As they proliferate and differentiate during follicular development, GCs can synthesize a variety of hormones and growth factors, and they express their receptors [19,20]. These substances regulate the growth, differentiation and maturation of follicular inner membrane cells and oocytes through gap junctions, and then, they regulate follicular development [21].…”
Section: Introductionmentioning
confidence: 99%